SWOT ANALYSIS OF SAINSBURY’S SUPERMARKET - RAJA SHARAH FATRICIA (Jurnal Manajemen Terapan dan Keuangan, 2016)
Sainsbury’s is the second largest supermarket chain in the UK after Tesco. However, Sainsbury’s has been losing market share to its competitors, the biggest grocery retailer, Tesco and ASDA, the US retailer, which has a market share of 17% now.  Hence, in order to increase its market share, Sainsbury’s made a new strategic step by joining Nectar Loyalty Program. The Nectar loyalty program is a crucial part of the strategy of Sainsbury’s. The retailer was convinced that a strong and attention-getting new rewards program could help in improving current market position. The main advantages of using the Nectar Card were based on the ease of achieving rewards by collecting points into one combined account. After one year, Nectar’s collector base was already bigger than the collector base of its largest competitor, Tesco. In addition, based on the satisfaction survey, most of the Nectar’s collectors rated Nectar as better than other loyalty programs. Nectar offers Sainsbury’s detailed information about what their customers are doing day-to-day. Sainsbury’s can use  this information to decide which stock to convey in which stores. The Nectar also helps Sainsbury’s in better and more efficient targeting of its customers. The Nectar program that is based on partnership among various sponsors has some advantages and some drawbacks compared to a single vendor loyalty program, like the program of Tesco. Sainsbury’s, as the most important sponsor, has profited from the participation in the program in customer lift, acquisition, retention and up-selling. Now, it is highest time for Sainsbury’s to decide, whether Nectar is the most suitable strategic approach to respond to recent changes in its market position Therefore, the problem statement originating from the case study is as follows: Should Sainsbury’s stay with the Nectar loyalty program in order to gain market share of 5% and increase average share of wallet of its customers by 10% in the upcoming 5 years?